2022
DOI: 10.3390/covid2030026
|View full text |Cite
|
Sign up to set email alerts
|

Early Discharge from a Newborn Nursery in the United States during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic changed birth hospitalization, with many hospitals implementing restrictions. Little is known about the impact of the COVID-19 pandemic on rates of early newborn discharge and length of stay (LOS). The primary objective was to compare rates of early discharge before and after the start of the COVID-19 pandemic. Secondary objectives included 28-day readmissions and LOS. A single-center retrospective cohort study was undertaken of all live newborns discharged from a well newborn nursery in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…This was expected due to hospital policy changes that encouraged earlier discharge and is consistent with prior studies. 17,18 Our data showed that among readmitted infants, those in the pandemic group were more likely to be rehospitalized within 7 days of discharge from the newborn nursery, but this was no longer true for infants readmitted at 30 days. This suggests differences between the prepandemic and pandemic groups were more likely to be due to factors in the first 1 to 2 weeks of life.…”
Section: Discussion/conclusionmentioning
confidence: 75%
See 2 more Smart Citations
“…This was expected due to hospital policy changes that encouraged earlier discharge and is consistent with prior studies. 17,18 Our data showed that among readmitted infants, those in the pandemic group were more likely to be rehospitalized within 7 days of discharge from the newborn nursery, but this was no longer true for infants readmitted at 30 days. This suggests differences between the prepandemic and pandemic groups were more likely to be due to factors in the first 1 to 2 weeks of life.…”
Section: Discussion/conclusionmentioning
confidence: 75%
“…17 Similarly, a small retrospective cohort study in Iowa found infants born during the pandemic had fewer rehospitalizations and shorter newborn nursery LOS. 18 Though not achieving statistical significance, both studies demonstrated trend toward different rates of rehospitalization diagnosis. 17,18 Further studies are needed to examine if there are similar findings in an urban, underserved community, particularly in one that was disproportionally affected early in the pandemic.…”
Section: Background and Significancementioning
confidence: 86%
See 1 more Smart Citation
“…Pandemic-specific factors may have contributed to our findings as the risk of newborn rehospitalization may have changed during this time. While some studies suggest that the frequency of overall post-discharge newborn rehospitalization did not change during the pandemic [28,29], there have been reports of increased rehospitalization risk in some subgroups such as those born to nulliparous mothers [30] and those readmitted for hyperbilirubinemia [31]. One nation-wide study from England found that while acute care presentations decreased by 16.7% overall during vs. before the pandemic, attendance for feeding problems and neonatal jaundice increased by 7.5% and 12.8% respectively [32].…”
Section: Discussionmentioning
confidence: 99%